GW24-e2233 Mapping, verification and ablation of the recurrence left atrial polycyclic reentry atrial flutter after ablation of persistent atrial fibrillation. (1st October 2013) - Yong-hua, Zhang; Xi, Su; Jing-lin, Zhang; Zhen, Li; Hong-wei, Han; Pin, Jiang; Chen, Tang
Abstract : Objectives: Introduce the method of mapping, verification and ablation the recurrence left atrial polycyclic reentry atrial flutter (AFL) after ablation of persistent atrial fibrillation (PsAF). Methods: 14 patients (9 men) with left atrial polycyclic reentry AFL after ablation of PsAF were enrolled [mean age 52.3 + /-10.4 years]. Electroanatomic mapping of the left atrium was conducted during tachycardia. Activation maps were used to identify the mechanism of AFL. Entrainment maps were used to verify the truth of AFL. RFCA was performed tageting the key isthmus to stop the tachycardia. Results: AFL mechanisms were identified as following: double-loop macroreentrant AFL around the mitral valve ring (MV) and left pulmonary vein (LPV) ring in 6 patients; Around the MV and right pulmonary vein (RPV) in 2 cases. Around the mitral valve ring and the former wall scar area in 2 cases. Around LPV and the former wall scar area in 2 cases. 1 case around the double PV; 1 around MV and the double potential (DP) zone. Entrainment mapping was used at the reentry ring to verify the truth before linear ablation. Immediate ablation success was achieved in all cases, 3 cases suffered from recurrent AT during the follow-up. Successful reablation procedure was achieved in all 3 cases. Conclusions: Atrial widely ablation can form complex after atrial arrhythmias. 3d electrophysiology mapping system help to determine arrhythmia electrophysiology mechanism, establishing ablation strategy reasonably, avoid iatrogenic arrhythmia caused by the improper ablation. MV-AFL for the present difficulties ablation, septal linear ablation can be considered as a kind of alternative methods of MV isthmus linear ablation.